Preparation of ZnO Nanoflowers for Surface Enhanced Raman Scattering Applications - Thi Ha, Tran; Manh Hong, Nguyen; Hanh, Mai Hong; Thanh, Pham Van; Doanh, Sai Cong; Thanh Binh, Nguyen; Nguyen Hai, Pham; Tam, Nguyen Trong; Hieu, Ho Khac; Tuyen, Nguyen Viet (VNU Journal of Science: Mathematics - Physics; Vol 36 No 1DO - 10.25073/2588-1124/vnumap.4369, 2020)
Thanks to unique Raman spectra of chemical substances, a growing number of applications in environmental and biomedical fields based on Raman scattering has been developed. However, the low probability of Raman scattering hindered its potential development and thus, many different techniques were developed to enhance Raman signal. A key step of surface-enhanced Raman scattering technique is to prepare active SERS substrate from noble metals. The main enhancement mechanism is electromagnetic enhancement resulted from surface plasmon resonance. The disadvantages of nanoparticles based SERS substrates include high randomness due to self - assembly process of nanoparticles. Recently, a new kind of SERS substrates with order nanostructures of semiconductors combining with noble metals can serve as active SERS substrates, which are expected to possess high enhancement of Raman signals. In this study, ordered ZnO nanorods were first prepared by galvanic hydrothermal method and gold was sputtered on the as prepared ZnO nanomaterials to enhance Raman. Our SERS substrates exhibit promising high enhancement factors and can detect chemical substances at concentration in nano molar range.